Implementation of Problem-Based Learning Based on Mathematical Literacy to Improve Student’s Higher-Order Thinking Skills - Rahmawati, Astri Eka; Lusiana, Restu; Utami, Sri Wahyu (Jurnal Pendidikan Matematika (JUPITEK), 2025)
HOTS are high-level thinking skills that are important to have in the era of globalization to solve complex problems. However, many students still have relatively low HOTS, especially when the issue is relevant to everyday life. This study aims to see the effectiveness of implementing Problem-Based Learning (PBL) based on mathematical literacy in improving students' HOTS in class X MP 2 students of SMK Negeri 5 Madiun. This study is a classroom action research (CAR) carried out in two cycles, with 29 subjects from class X MP 2 SMK Negeri 5 Madiun. Each research cycle consists of four stages: planning, implementing actions, observation, and reflection. The main objective of this study is to determine whether implementing Problem-Based Learning (PBL) based on mathematical literacy can improve students' HOTS in mathematics learning. The study results showed a significant increase in students' HOTS after the implementation of PBL based on mathematical literacy. In the pre-cycle stage, students' HOTS was at 56.6%. After the actions were carried out in cycle I, students' HOTS increased to 71.8%, although it had not reached the expected completion criteria. In cycle II, there was another increase in students' HOTS to 79.2% which met the success criteria